Financial Ratios And Stock Return In The Food & Beverage Sector - Sunaryo, Deni; Ibrahim, Mukdad; Lestari, Etty Puji; Puryandani, Siti (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
This study uses a quantitative approach with panel data analysis to examine the effect of financial ratios on stock return and the role of financial distress as a moderating variable. The sample consists of companies in the food and beverage processing sector listed on the Indonesia Stock Exchange (IDX) during the period from 2013 to 2023. The data used were obtained from the annual financial statements published by these companies, as well as stock market data from the IDX. The total sample used in this study consists of 121 data points obtained through purposive sampling from 26 companies that met the research criteria. The dependent variable in this study is stock return, which is calculated based on the annual stock price change divided by the stock price at the beginning of the year. The independent variables include financial ratios, namely Total Asset Turnover (TAT), Price Earnings Ratio (PER), and Times Interest Earned Ratio (TIER). Financial distress is measured using the Altman Z-Score, which serves as the moderating variable in this study. Multiple regression analysis was used to test the research hypotheses, incorporating interaction variables between financial ratios and financial distress to test for moderating effects. The tests included descriptive analysis, normality test, multicollinearity test, and autocorrelation test to ensure the validity of the results.The results show that TAT, PER, and TIER have weak or insignificant effects on stock return, with TAT and TIER showing negative but statistically insignificant relationships. Financial distress was found to moderate the relationship between TIER and stock return in certain models, although it did not show a significant effect in other models. This study emphasizes the need for further research to include macroeconomic variables and explore industry sector dynamics to deepen the understanding of this relationship.